Identifikasi Faktor–Faktor Penyebab Cost Overrun dan Time Overrun pada Proyek Konstruksi Gedung Di Kota Banda Aceh - Soviana, Widya; Herlina, Eva; Soviati, Sukma; Musrian, Andi (Tameh, 2022)
Projects of building construction develops acordance with the implementation of the fulfillment of human life. During implementation, the project did not always as expected. These things happen due to cost and time deviations. The problem in this research is what are the factors that cause cost overrun and time overrun in the implementation of building construction projects in Banda Aceh city. The purpose of the study was to determine the causes of cost overrun and time overrun in the implementation of building construction projects toward minimize the impact of failure in the implementation of a construction project. The research data was obtained by distributing questionnaires to 40 respondents from qualified (small) and (medium) of contractors in Banda Aceh city. The sampling technique used is purposive sampling with the criteria of fulfilling the experience of having been involved in the implementation of building construction projects. Data processing was carried out with SPSS version 24 software with confirmatory factor analysis, descriptive analysis and fishbone analysis. The results of factor analysis obtained the average value of the MSA test of 0.694, the KMO test of 0.684. The value of a variable can be analyzed further if the value exceeds 0.5 and the Bartlett test obtained a value of 0.000 <0.05, it explaned each variable is correct. The total value of variance explained is 50.91%, it means the nine factors can form the factors causing cost overrun and time overrun, while the remaining 49.08% is explained by other factors. From the loading factor value, the dominant factor is material factor (X4) with a loading value of 0.91. The results of the descriptive analysis show causing of cost overrun and time overrun are an increase in material prices (X4.3) with mean value is 4.13 and poor quality control of materials (X4.4) with mean value is 4.03.